(untitled) (Research, Society and Development, 2022)
The arboviruses Dengue, Chikungunya and Zika virus are present in several tropical regions and are transmitted by the Aedes aegypti mosquito. The containment of these diseases is done by fighting the vector, usually using chemical insecticides, such as organophosphates and organochlorines. These provoke the resistance of the transmitter, have a high accumulation rate in the body of non-target populations, and promote the contamination of ecosystems. The application of materials of natural origin with larvicidal activity, such as essential oils, is a promising alternative to replace the use of chemical insecticides. In this systematic review, we sought to present the larvicidal properties of essential oils from botanical species of Brazilian flora against Ae. aegypti. The search resulted in 36 papers selected as articles of interest. The 65 plants described in the selected articles showed larvicidal activity mostly excellent (27 were classified as strongly active) or satisfactory (13 were moderately active, and 24 were effective), while only one was inactive. The species that showed the highest larvicidal activity were: Anacardium occidentalis L. (0.01 ppm); Copaifera langsdorffii Desf. (0.04 ppm); Carapa guianensis Aubl. (0.06 ppm); Cymbopogon winterianus Jowitt. (0.10 ppm); Ageratum conyzoides L. (0.15 ppm); Tagetes minuta L. (0.21 – 0.25 ppm); and Siparuna guianensis Aubl. (1.76, 0.98 and 2.46 ppm). Studies on the essential oils of Brazilian plants are of great relevance to combat arboviruses. The Brazilian flora, despite its vast biodiversity, is still little known and explored, possessing a huge potential for the development of eco-friendly, environmentally safe, and low-cost products.